Common recessive limb girdle muscular dystrophies differential diagnosis: why and how? - Ana Cotta; Elmano Carvalho; Antonio Lopes da-Cunha-Júnior; Júlia Filardi Paim; Monica M. Navarro; Jaquelin Valicek; Miriam Melo Menezes; Simone Vilela Nunes; Rafael Xavier Neto; Reinaldo Issao Takata; Antonio Pedro Vargas (Arquivos de Neuro-Psiquiatria)
Limb girdle muscular dystrophies are heterogeneous autosomal hereditary neuromuscular disorders. They produce dystrophic changes on muscle biopsy and they are associated with mutations in several genes involved in muscular structure and function. Detailed clinical, laboratorial, imaging, diagnostic flowchart, photographs, tables, and illustrated diagrams are presented for the differential diagnosis of common autosomal recessive limb girdle muscular dystrophy subtypes diagnosed nowadays at one reference center in Brazil. Preoperative image studies guide muscle biopsy site selection. Muscle involvement image pattern differs depending on the limb girdle muscular dystrophy subtype. Muscle involvement is conspicuous at the posterior thigh in calpainopathy and fukutin-related proteinopathy; anterior thigh in sarcoglycanopathy; whole thigh in dysferlinopathy, and telethoninopathy. The precise differential diagnosis of limb girdle muscular dystrophies is important for genetic counseling, prognostic orientation, cardiac and respiratory management. Besides that, it may probably, in the future, provide specific genetic therapies for each subtype.